A hybrid fuzzy evaluation method for curtain grouting efficiency assessment based on an AHP method extended by D numbers. (February 2016) - Fan, Guichao; Zhong, Denghua; Yan, Fugen; Yue, Pan
Highlights: A hybrid fuzzy evaluation method for curtain grouting efficiency assessment is proposed. The proposed method can assess curtain grouting efficiency from the perspectives of both permeability and tightness. The D-AHP method can effectively represent and address uncertain information and make weighting more scientific. This study reveals that low permeability does not guarantee high grouting efficiency. Abstract: Curtain grouting is designed to create a hydraulic barrier that reduces water seepage under a dam foundation. However, due to the inability of observing grout penetration in the fractures and voids under a dam foundation, it is difficult to assess grouting effectiveness. Existing single-factor evaluation methods, including in situ water pressure tests (WPT), numerical modeling and experiments, cannot estimate the grouting efficiency from the perspectives of both permeability and tightness. This paper proposes a hybrid fuzzy comprehensive evaluation method to assess curtain grouting efficiency by considering both the permeability and tightness of a grout curtain. Permeability (LU), Rock Quality Designation (RQD), and the Fracture Filled Rate (i.e., the ratio of the fractures filled by grout, FFR), as derived from water pressure tests, core specimen drilling and borehole television imaging, are the key assessment parameters of grouting efficiency. A three-level hierarchical model of curtain grouting efficiency assessment is established that considers permeability and tightness as criteria and LU, RQD and FFR as alternatives. Because determining the weights of the alternatives is a fuzzy and uncertain problem, the D-AHP method, which extends traditional AHP with D numbers and can handle uncertain problems more effectively, is introduced to determine the weights of the alternatives. The detailed procedures of the proposed hybrid evaluation method are demonstrated step by step. A case study is presented to evaluate the curtain grouting efficiency of a hydropower project in China. The results indicate that low permeability does not result in high grouting efficiency because although the RQD and FFR may be very low, only low permeability, high RQD and high FFR indicate high grouting efficiency. The proposed method provides a detailed understanding of grouting efficiency evaluation; with the help of an efficiency index (EI), the grouting efficiency of grouted units or areas can be easily marked and classified.